Aktivitas Larvasida Berbagai Pelarut pada Ekstrak Biji Kayu Besi Pantai (Pongamia pinnata) terhadap Mortalitas Larva Aedes spp. - Yuneu Yuliasih; Mutiara Widawati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
The use of chemical compound as a way to control DHF may cause harmful effect for humans and environment. It is necessary to develop biological insecticides derived from plants such as Pongamia pinnata. This study was designed to determine the larvicidal activity of P. pinnata seeds extract with various solvent on Aedes spp. This study was an experimental research with post test only control group design. Materials used in the research were P. pinnata seed extracts with water, methanol and chloroform solvents of concentration; 100 ppm, 200 ppm, 300 ppm, 400 ppm and 500 ppm. Larvicidal activity of P. pinnata seed extracts was tested against third instar larvae of Ae. aegypti and Ae. albopictus, 24 hours observation was carried out within each treatment.very test was repeated for 3 times. The result showed that larvae mortality was found in the methanol extract with LC50 value of 141.88 ppm for Ae. aegypti and 108.19 for Ae. albopictus, and in the chloroform extract with LC50 value of 346.06 ppm for Ae. aegypti and 222.29 ppm for Ae. albopictus. The water extract of P. pinnata seed was not effective as a larvicidal, while methanol and chloroform of P. pinnata seed extracts act as potential natural insecticide.